Measuring Lp(a) particles with a novel isoform-insensitive immunoassay illustrates efficacy of muvalaplin - Craig A. Swearingen; John H. Sloan; Grace M. Rhodes; Robert W. Siegel; Nico Bivi; Yuewei Qian; Robert J. Konrad; Michael Boffa; Marlys Koschinsky; John Krege; Giacomo Ruotolo; Stephen J. Nicholls; et al. (Journal of Lipid Research)
Lipoprotein(a) [Lp(a)] is a cardiovascular risk factor, and there is considerable interest in developing Lp(a)-lowering therapeutics for cardiovascular prevention. Current commercial Lp(a) assays measure total apolipoprotein(a) [apo(a)] and may be insufficient to accurately measure Lp(a) concentrations and determine Lp(a) lowering by a new class of small-molecule Lp(a) formation inhibitors such as muvalaplin. We developed a novel immunoassay that measures only Lp(a) particles. This intact Lp(a) assay demonstrated robust analytical performance, was insensitive to apo(a) isoform size, and correlated with a liquid chromatography–tandem mass spectrometry method. Muvalaplin phase I multiple ascending dose study samples and lepodisiran, a small-interfering RNA that lowers Lp(a), phase I single ascending dose study samples were analyzed using the intact Lp(a) assay and commercial assays. The Lp(a)-lowering efficacy of muvalaplin was underestimated by the commercial assay measuring total apo(a) compared with the intact Lp(a) assay specifically measuring Lp(a) particles. In contrast, the Lp(a)-lowering effect of lepodisiran was clinically comparable between the intact Lp(a) assay and commercial assay. This novel intact Lp(a) assay provides a more accurate approach for the assessment of Lp(a)-lowering agents and the study of Lp(a)-associated risk compared with currently available assays.